2014
DOI: 10.1136/ejhpharm-2014-000486
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist prescribing within a UK NHS hospital trust: nature and extent of prescribing, and prevalence of errors

Abstract: Objectives Suitably qualified pharmacists in the UK are able to prescribe all medicines. While doctors' prescribing errors are well documented, there is little information on the rate and nature of pharmacists' prescribing errors. Our aim was to measure the prevalence of prescribing errors by pharmacists. Methods Prescribing by pharmacists, for inpatients admitted to three hospitals in North East England was studied. Part one measured the extent of prescribing by pharmacists as a proportion of all prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 13 publications
3
40
0
Order By: Relevance
“…A study by Baqir and colleagues [Baqir et al 2014] focused on the nature and extent of prescribing and prevalence of errors by pharmacist NMPs, specifically within a UK NHS hospital. Results from this study demonstrated an error rate of 0.3% of medication orders generated by pharmacist prescribers.…”
Section: Impact Of Nonmedical Prescribingmentioning
confidence: 99%
“…A study by Baqir and colleagues [Baqir et al 2014] focused on the nature and extent of prescribing and prevalence of errors by pharmacist NMPs, specifically within a UK NHS hospital. Results from this study demonstrated an error rate of 0.3% of medication orders generated by pharmacist prescribers.…”
Section: Impact Of Nonmedical Prescribingmentioning
confidence: 99%
“…Electronic medical notes were then individually reviewed by VC (principal author and non-prescribing clinical pharmacist at foundation level in critical care pharmacy practice10) for further details on the indication of pharmacist prescribing and data related to second pharmacist ‘clinical check’ activity. The indications for pharmacist prescribing were recorded and categorised according to a 2014 survey of critical care pharmacist practice3 and a 2014 study of pharmacist prescribing in general hospital practice 8. The medicine prescriptions were categorised according to the primary indication for prescribing with determination from the medical note entry.…”
Section: Methodsmentioning
confidence: 99%
“…15e17 While there are limited data, one study of pharmacist prescribing in hospitals in England reported error prevalence of 0.3% of prescriptions written. 18 The scope of pharmacist prescribing in hospital is developing continually. Hospital pharmacists prescribe in a diverse range of clinical specialities including acute medicine, antimicrobials, cardiology, diabetes, hypertension, mental health, neurology, pain management, oncology, orthopaedics and respiratory.…”
Section: Introductionmentioning
confidence: 99%